THE POTENTIAL OF SOUTH AFRICAN MEDICINAL ORCHIDS - Chinsamy, M.; Finnie, J.; van Staden, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Orchidaceae is represented by approximately 20 000 species worldwide across a wide range of habitats. They have a broad range of ethnobotanical applications. Southern Africa supports approximately 494 species, of which an estimated 49 feature significantly in South African traditional medicine. We attempted to assemble significant ethnobotanical information available from the literature detailing the uses, preparations and administration of South African orchids in African traditional medicine. In order to address the lack of pharmacological, toxicological and phytochemical knowledge, the use of orchids elsewhere in the world is compared with their uses in South Africa. Antimicrobial and anti-inflammatory activity may be present in South African orchid species: Ansellia africana used to treat coughs; Eulophia sp. are applied to sore limbs or as poultice to treat pain; Polystachya ottoniana are used to soothe pain associated with teething in babies and to treat diarrhoea; and Satyrium bracteatum used to treat intestinal worms. Further examples will be discussed. By encouraging the scientific validation of South African medicinal orchid use, conservation efforts would benefit greatly as it may add value to these species. It also provides an incentive for further research initiatives, with an emphasis on essential cultivation techniques.